2013
DOI: 10.5232/ricyde2013.03204
|View full text |Cite
|
Sign up to set email alerts
|

Valoración de alumnado y profesorado de educación física tras la aplicación de dos modelos de enseñanza. (Students and teachers’ perception after practice with two pedagogical models in physical education).

Abstract: Existe suficiente cantidad de estudios comparativos sobre modelos de enseñanza en educación físi-ca que utilizan diseños pre o cuasi experimentales. Sin embargo, no son tantos los que emplean algunas tipologías propias de estos diseños. Se pretende por ello comparar, desde la perspectiva de alumnos y de su profesor especialista, el modelo de Educación Deportiva con el modelo Tradicional. Para ello se utilizó un diseño cruzado simple de grupos aleatorios, en el que se aplicaron los dos niveles de la variable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
18

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 53 publications
(15 reference statements)
2
2
0
18
Order By: Relevance
“…These findings corroborate Sport Education as a format of achieving significant improvements in learning and performance in a sports setting as they have shown in physical education (Calderón, Martínez de Ojeda, and Hastie, 2013;Hastie and Sinelnikov, 2006;Pritchard et al, 2008;Sinelnikov et al, 2008). Moreover the results found by Stran and Curtner-Smith (2010), and Wallhead, Hagger, and Smith (2010) are corroborated; because they applied Sport Education in different age groups and all improved the learning.…”
Section: Discussionsupporting
confidence: 77%
“…These findings corroborate Sport Education as a format of achieving significant improvements in learning and performance in a sports setting as they have shown in physical education (Calderón, Martínez de Ojeda, and Hastie, 2013;Hastie and Sinelnikov, 2006;Pritchard et al, 2008;Sinelnikov et al, 2008). Moreover the results found by Stran and Curtner-Smith (2010), and Wallhead, Hagger, and Smith (2010) are corroborated; because they applied Sport Education in different age groups and all improved the learning.…”
Section: Discussionsupporting
confidence: 77%
“…Es un modelo basado en el trabajo en equipo y la cesión de responsabilidades al alumnado para el trabajo sobre la autonomía . Se ha visto que, entre otras cosas, el modelo de Educación Deportiva aumenta la percepción del aprendizaje y la satisfacción del alumnado (Calderón, Martínez de Ojeda, y Hastie, 2013), fomentando el clima motivacional de clase orientado a la tarea (Cuevas, García-López, y Conteras, 2015) y logrando mejorar el nivel de habilidad y de conocimiento táctico de estudiantes considerados de baja-habilidad (Hastie, 1998).…”
Section: Introductionunclassified
“…Attending to the gender, the results showed that boys and girls that participated in the SE model were more active than girls and boys that participated in the DI. It could be because the students that participated in a lesson plan with DI, where the teacher have a central role, lost the interest for the practice of PA (Calderón, Martínez de Ojeda, and Hastie, 2013) while in the SE model, the students play a more active role in class (Farias, Mesquita, and Hastie 2015).…”
Section: Gender Physical Activity Levels In Sport Education and Direcmentioning
confidence: 99%